Development of a dosimetry system for therapeutic X‐rays using a flexible amorphous silicon thin‐film solar cell with a scintillator screen. Issue 7 (18th April 2022) - Jeong, Seonghoon; Cheon, Wonjoong; Shin, Dongho; Lim, Young Kyung; Jeong, Jonghwi; Kim, Haksoo; Yoon, Myonggeun; Lee, Se Byeong
Abstract: Purpose: To evaluate the dosimetric characteristics and applications of a dosimetry system composed of a flexible amorphous silicon thin‐film solar cell and scintillator screen (STFSC‐SS) for therapeutic X‐rays. Methods: The real‐time dosimetry system was composed of a flexible a‐Si thin‐film solar cell (0.2‐mm thick), a scintillator screen to increase its efficiency, and an electrometer to measure the generated charge. The dosimetric characteristics of the developed system were evaluated including its energy dependence, dose linearity, and angular dependence. Calibration factors for the signal measured by the system and absorbed dose‐to‐water were obtained by setting reference conditions. The application and correction accuracy of the developed system were evaluated by comparing the absorbed dose‐to‐water measured using a patient treatment beam with that measured using the ion chamber. Results: The responses of STFSC‐SS to energy, field size, depth, and source‐to‐surface distance (SSD) were more dependent on measurement conditions than were the responses of the ion chamber, although the former dependence was due to the scintillator screen, not the solar cell. The signals of STFSC‐SS were also dependent on dose rate, while the responses of solar cell alone and scintillator screen were not dependent on dose rate. The scintillator screen reduced the output of solar cell at 6 and 15 MV by 0.60 and 0.55%, respectively. The different absorbed dose‐to‐water measured using STFSC‐SS for patient treatment beam differed by 0.4% compared to those measured using the ionization chamber. The uncertainties of the developed system for 6 and 15 MV photon beams were 1.8 and 1.7%, respectively, confirming the accuracy and applicability of this system. Conclusions: The thin‐film solar cell‐based detector developed in this study can accurately measure absorbed dose‐to‐water. The increased signal resulting from the use of the scintillator screen is advantageous for measuring low doses and stable signal output. In addition, this system is flexible, making it applicable to curved surfaces, such as a patient's body, and is cost‐effective.